Problems of Social, Economic, and Educational – Case in “Kampung Ketupat” (Samarinda City, Indonesia) - Kurniawan A., Erwin; Hasid, Zamruddin; Fitriadi, Fitriadi (Budapest International Research and Critics University, 2021)
Environmental changes in an area have shaped the character of the community. A growing culture always determines the economic, social, and environmental development that faces the extent to which per capita welfare can increase. This study tries to concentrate on the description of socio-economic life, the level of education, and the extent to which the condition is with the level of public education. The method is qualitative with the technique of Miles & Huberman (1994). The objectivity of the study lies in ketupat craft-workers in “Kampung Ketupat” (Samarinda Seberang District), where we focused through in-depth interviews during August 2020 - September 2021 with 55 informants. We found that the socio-economic conditions of the craftworkers were still low. Broadly, the educational level of ketupat craftworkers is also low. We can see this from the basic education of those who do not go to school and, on average, only reach the junior high school (SMP) level. There is a tendency that the higher the economic and educational level of children of ketupat craft-workers, can be the key to success amid today’s global competition. The findings have implications for highlighting vital factors such as income, social, and education that could have a significant impact on the revitalization of their well-being.